المناطق الحرة في العراق "الواقع والتحديات" (المجلة العراقية للعلوم الاقتصادية, 2018)
Nations have been interested in the free zones as one of the successful means to attract foreign investments and for their contribution in providing job opportunities, bring newand advanced technology, increase the resources of the state of foreign exchange, increasing exports, and is one of the successful means to achieve economic and social goals. The experiences of the free zones vary from state to state, depending on their structures, policies, economic and social conditions, security, types of management and the availability of an appropriate climate for investment.In the Arab world,it has been thrust to the establishment of free zones in many countries, including Jordan, Egypt and the United Arab Emirates.These countries have been selected in the research to take advantage of the positive results achieved in the area of ​​free zones for the development of the free zones of Iraq.In Iraq,it has been thrust to the establishment of the Iraqi General Authority for Free Zones, under Law No. (3) for the year 1998, and in spite of what Iraq possessed of the elements of the success of the free zones of the geographical location and the vast market and the low costs and availability of labor, but it did not reach the ranks of those of the successful free zones, so the study has tended to examine the legislative environment in Iraq, as one of the important ingredients for the success of the free zones of Iraq, what are the synergies and conflicts between the General Authority for Free Zones and the National Investment Commission, what are the possible effects of free zones on investment, what are the possible effects of free zones on the Iraqi economy, What are the requirements for the development of the free zones of Iraq, what are the ways to benefit from the experiences of countries that have been studied in the area of ​​free zones, and the development of proposals for the establishment of free zones in the Iraqi provinces.The study has reached that it is necessary for local governments, regional governments and bodies provinces to tend towards the establishment of free zones within their territorial boundaries of what the investment of the positive financial, economic and social effects.